1993
DOI: 10.1016/0248-4900(93)90109-r
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fluorochromes for cellular structure and function studies by flow cytometry

Abstract: Because flow cytometry permits the analysis of individual whole cells, one of the key requirements in selecting a probe is its ability to target the site of interest into cells. In addition, dyes must possess ideal properties (ie extinction coefficient, Stoke's shift) rendering them appropriate for this methodology. Other characteristics, such as fluorescence quenching and energy transfer, inherent to the staining, provide numerous applications in flow cytometry. The available fluorophores used in flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 185 publications
(160 reference statements)
0
47
0
Order By: Relevance
“…Acridine orange is an intercalating dye that emits orange/red fluorescence when interacting with single-stranded nucleic acids, and fluoresces green when interacting with double-stranded nucleic acids. Even though this characteristic has been used to measure RNA in bacterial samples (Nishimura et al, 1995), the stain is very sensitive to the conditions of use, and tends to bind nonspecifically (Petit et al, 1993). Some of the DNA stains have shown differential binding to AT (DAPI, HOECHST) or to GC (chromomycin, mithramycin and olivomycin) base pairs, and combination of both types of dyes has been used to measure the %GC content of bacterial cultures and as an additional characteristic for classification (van Dilla et al, 1983).…”
Section: Bacterial Detection After Stainingmentioning
confidence: 99%
“…Acridine orange is an intercalating dye that emits orange/red fluorescence when interacting with single-stranded nucleic acids, and fluoresces green when interacting with double-stranded nucleic acids. Even though this characteristic has been used to measure RNA in bacterial samples (Nishimura et al, 1995), the stain is very sensitive to the conditions of use, and tends to bind nonspecifically (Petit et al, 1993). Some of the DNA stains have shown differential binding to AT (DAPI, HOECHST) or to GC (chromomycin, mithramycin and olivomycin) base pairs, and combination of both types of dyes has been used to measure the %GC content of bacterial cultures and as an additional characteristic for classification (van Dilla et al, 1983).…”
Section: Bacterial Detection After Stainingmentioning
confidence: 99%
“…Carboxyfluorescein diacetate is a nonpolar lipophilic compound that passes into the cell and is enzymatically cleaved by nonspecific esterases inside the cell with the formation of fluorescent carboxyfluorescein. Carboxyfluorescein is polar and is retained in viable cells with intact cytoplasmic membrane (Petit et al 1993). Although the antibacterial activity of EO from plants has been widely reported (Nychas 1995;Tassou et al 2000), their mode of action against bacteria has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Of the characteristics of fluorochromes important to increase their sensitivity, i.e., Stokes' shift, extinction coefficient, quantum yield, fluorescence lifetime, and photobleaching characteristics (24,25), increasing the Stokes' shift appears to have the most potential with environmental samples. This is because the emission spectrum of the fluorochrome versus that of the background sources also needs consideration.…”
Section: Discussionmentioning
confidence: 99%
“…FRET can be designed to have a large Stokes' shift; viz. the difference between the absorption and emission maxima (11,25), which is probably the most important feature to increase the sensitivity of a fluorescence detection method. Petit et al (25) suggested that the Stokes' shift should be at least 20 nm, and Vesey et al (26) showed that for any excitation wavelength of 300 -700 nm, the autofluorescence emission intensity decreased with increasing excitation.…”
Section: Discussionmentioning
confidence: 99%